2013
DOI: 10.1016/j.is.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

How collaborative technology supports cognitive processes in collaborative process modeling: A capabilities-gains-outcome model

Abstract: We examine which capabilities technologies provide to support collaborative process modeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 60 publications
0
40
0
1
Order By: Relevance
“…Based on their findings, they advocate to adapt guidance measures dynamically to the participants' level of expertise. Recker et al (2013) have shown that tool support for collaboration during modeling can help to gather and extend knowledge of participants about both, the modeled domain and the modeling method. Their results indicate that easy to use technology support is required for collaboration and modeling is required to enable participants to contribute.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their findings, they advocate to adapt guidance measures dynamically to the participants' level of expertise. Recker et al (2013) have shown that tool support for collaboration during modeling can help to gather and extend knowledge of participants about both, the modeled domain and the modeling method. Their results indicate that easy to use technology support is required for collaboration and modeling is required to enable participants to contribute.…”
Section: Related Workmentioning
confidence: 99%
“…-F1: Individual understanding is codified in separate models by each actor and consolidated in a separate step (Türetken and Demirörs 2011;Rittgen 2009b;Engelmann and Hesse 2010;Dean et al 2000; Groeben and Scheele 2000) -F2: Divergent understandings among the involved actors are identified and explicitly made visible (Herrmann et al 2004b;Rittgen 2009b;Stoyanova and Kommers 2002;Fischer et al 2002;Heiser et al 2004; Türetken and Demirörs 2011) -F3: The process of consolidation requires procedural guidance (Herrmann et al 2004b;Rittgen 2009b;Dean et al 2000;Hjalmarsson et al 2015;Gassen et al 2015;Hoppenbrouwers and Rouwette 2012;Stoyanova and Kommers 2002;Recker et al 2013;Front et al 2015) -F4: The used modeling language must be adequate for the intended target group and appropriate for the aim of modeling (Herrmann et al 2004b;Pino et al 2008;Fahland and Weidlich 2010;Kabicher and Rinderle-Ma 2011;Zarwin et al 2014;Malavolta et al 2013;Groeben and Scheele 2000;Fischer et al 2002;Davies et al 2006;Zugal et al 2013;Front et al 2015) When reviewing the four approaches pursuing similar objectives described above in the light of these properties, their different foci become clearly visible (cf. Table 1).…”
Section: Related Workmentioning
confidence: 99%
“…In further research, Pinggera et al (2013) examined, how to use eye movement analysis to investigate the activities of individuals involved in a collaborative modeling process. Recker et al (2013) propose an approach that focusses on cognition of the actors involved in collaborative modeling and collect data using an ex-post questionnaire (i.e. do not observe the modeling process directly).…”
Section: Available Approaches For Evaluating Collaborative Modelingmentioning
confidence: 99%
“…These works argue for the need of assessing the development of understanding about the modeled topic, as the understanding of a topic ultimately affects the actions performed in the real world. Several authors have addressed this issue from a cognitive perspective, focusing on the development of understanding on the subject of modeling for individual modelers (Claes et al 2015;Recker et al 2013;Soffer et al 2012). They, however, either focus on examining the modeling process of individual modelers confronted with artificial tasks in an experimental setting (Claes et al 2015;Soffer et al 2012) or examine collaborative modeling processes ex-post using questionnaires (Recker et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation